2014
DOI: 10.1016/j.compscitech.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection and self-repair in hollow glass fiber fabric-reinforced epoxy composites via fiber filling

Abstract: 2Hollow glass fiber reinforced epoxy matrix composites were produced to study whether the damage development can be followed and the self-repair can triggered by filling the fibers with suitable additives. Composite plates were manufactured by the hand layup and vacuum assisted resin transfer molding techniques. To detect subcritical transverse impact damage, hollow fibers were filled with an ultraviolet fluorescent dye, whereas for selfrepair, they were filled with a polyester resin along with the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 23 publications
0
45
1
Order By: Relevance
“…In the latter case the stoichiometric ratio should be considered by different amount or sizes of the related capsules to be deposited, which is a quite hard task. Due to this reasons the single capsule technique has certainly more chance to a successful application since these capsules may be added through a carrier resins that could be in principle different from the composite matrix [141]. To trigger the polymerization of such "matrix dissimilar" resins additional treatments (heating, UV or electron beam indication) may be needed.…”
Section: Capsule-based (Autonomous)mentioning
confidence: 99%
“…In the latter case the stoichiometric ratio should be considered by different amount or sizes of the related capsules to be deposited, which is a quite hard task. Due to this reasons the single capsule technique has certainly more chance to a successful application since these capsules may be added through a carrier resins that could be in principle different from the composite matrix [141]. To trigger the polymerization of such "matrix dissimilar" resins additional treatments (heating, UV or electron beam indication) may be needed.…”
Section: Capsule-based (Autonomous)mentioning
confidence: 99%
“…Ωx,i and Ωy,i determined for the xi and yi coordinates of each Pi are not averaged, but the individual Ex,i és Ey,I values are calculated with the corresponding CEi and averaged according to Equation (21). (20) Alternative to the average point method, the reciprocals of the Ω parameters calculated from the individual coordinates of the end-points are averaged here.…”
Section: Individual Coordinates Methodsmentioning
confidence: 99%
“…Fibre deflection tests were performed on solid and hollow glass fibres of 50 mm length earlier and evaluated using only the vertical displacements of the fibre ends. Results of these tests were reported earlier in [18], [21] and [23]. The essence of this method is that a fibre is clamped horizontally at one end ( Figure 1) and a vertical measuring scale is used to read the vertical displacement (fB=-yB) of the free fibre end with 0.5 mm precision.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the presence of HGF within a CFRP laminate produce minimal degradation in flexural strength and ply disruption. Recently, much thinner hollow glass fibers (13 !m outer diameter) were used in a damage-detecting and self-repairing epoxy composite to ensure major reinforcement [67]. Self-repair in this system was achieved by adding polyester resin (catalyzed resin and initiator) to the hollow fibers.…”
Section: Hollow Glass Fibers (Hgf) and Hollow Glass Bubbles (Hgb) As mentioning
confidence: 99%